IDDF2020-ABS-0077 Treatment patterns should be carefully chosen in different primary sites of GI-NECs. (18th November 2020) - Cai, Wen; Ge, Weiting; Wu, Dehao; Mao, Jianshan; Hu, Hanguang
Abstract : Background: Neuroendocrine carcinomas (NECs) are heterogeneous and aggressive in gastrointestinal tract (GI). However, treatment patterns and related outcomes in the different primary site have not been well described. Methods: The SEER data was selected from 2010 to 2016, and 5-year survival was set as the end-point. Coarsened exact matching (CEM) was performed to adjust before further regression models. Patients were separated by treatment groups and then comparing survivals for treatment patterns used multivariate analysis in different primary sites. Patients with non-chemotherapy and non-surgery were considered as the reference group. Results: 4114 patients with GI-NECs including stomach (12.96%), small intestinal (37.50%), colon (24.45%) and rectum (25.09%) were identified. In the stomach, chemotherapy without surgery will increase the risk of death in non-metastatic NEC patients (HR=3.11, 95%CI 1.26–7.76; P =0.014). Chemotherapy combining with primary resection will benefit metastatic patients (HR=0.15, 95%CI 1.26–7.76; P =0.017). In small intestinal, single primary resection will benefit both non-metastatic (HR=0.67, 95%CI 0.45–0.98; P =0.042) and metastatic (HR=0.61, 95%CI 0.41–0.92; P =0.018) patients younger than 60-year-old. In the colon, primary site resection combines with chemotherapy will benefit the metastatic patient (HR=0.41, 95%CI 0.18–0.95; P =0.039) comparing with other therapy combination. In the rectum, combining chemotherapy, radiotherapy, and primary surgery in non-metastatic patients will increase the risk of death (HR=2.11, 95%CI 1.14–4.00; P =0.022). Pooling all patients received metastatic sites resection and comparing with the reference group, metastatic sites resection in GI-NEC will bring survival benefits (HR=0.42, 95%CI 0.19–0.93; P =0.033). Conclusions: GI-NECs have different treatment patterns. Primary sites resection should be the basic treatment choices for GI-NECs. Chemotherapy should be cautious, especially in non-metastatic patients and considered more biological characteristics of NECs (eg: Ki-67) before using it. Patients with distant metastasis can benefit from metastatic sites resection.